Impact of tranexamic acid on bleeding during coronary artery bypass for patients under treatment of low molecular weight heparin - Doğukan, Mevlüt; Güler, Fahriye; Baysal, Ayşe; Güven, Cengiz; Uludag, Öznur (Journal of Surgery and Medicine, 2020)
Aim: Tranexamic acid (TA) is an antifibrinolytic agent that prevents the dissolution of fibrin clot. We investigated the impact of the use of tranexamic acid (TA) on bleeding for patients under treatment of low molecular weight heparin during coronary artery bypass graft (CABG) operations. Methods: Among 82 patients, 60 patients undergoing CABG with cardiopulmonary bypass (CPB) were enrolled into a case-control study within a six month-period. On the first postoperative day, patients were divided into two groups depending on the intraoperative use of TA. TA was not administered to control group patients (n=30) while those in the study group (n=30) received TA intravenously at a dose of 10 mg/kg. Coagulation variables including complete blood cell count, D-Dimer, fibrinogen, prothrombin time (PT), activated partial thromboplastin time (aPTT) and international normalized ratio (INR) values were collected preoperatively and 24 hours after surgery. Estimated blood loss, loss by drainage, total amounts of packed red blood cell and fresh frozen plasma transfusions were recorded. P-value <0.05 was considered statistically significant. Results: Among 60 patients included in the study, there were 39 and 21 males and females, respectively. The mean age of all patients was 61.6 years. The two groups were similar in terms of use of fresh frozen plasma, age, height, and weight (P=0.268, P=0.586, P=0.787, P=0.641, respectively). The amount of postoperatively transfused packed red blood cells in units were lower in the study group (P=0.04). Total mediastinal drainage amounts in the 4th, 8th, 12th hours and overall were lower in the study group (P=0.016, P=0.006, P=0.013, P=0.04, respectively). Conclusions: TA is a safe drug that reduces postoperative bleeding without side effects in patients using DMAH undergoing CABG operations.